Developmental Differentiation and Binding of Mental Processes with g through the Life-Span - Demetriou, Andreas (J Intell, 2017)
Integration/differentiation of mental processes is major mechanism of development. Developmental theories ascribe intellectual development to it. In psychometric theory, Spearman’s law of diminishing returns postulates that increasing g allows increasing differentiation of cognitive abilities, because increased mental power allows variable investment in domain-specific learning. Empirical evidence has been inconsistent so far, with some studies supporting and others contradicting this mechanism. This state of affairs is due to a developmental phenomenon: Both differentiation and strengthening of relations between specific processes and g may happen but these changes are phase-specific and ability-specific, depending upon the developmental priorities in the formation of g in each phase. We present eight studies covering the age span from 4 to 85 years in support of this phenomenon. Using new powerful modeling methods we showed that differentiation and binding of mental processes in g occurs in cycles. Specific processes intertwine with g at the beginning of cycles when they are integrated into it; when well established, these processes may vary with increasing g, reflecting its higher flexibility. Representational knowledge, inductive inference and awareness of it, and grasp of logical constraints framing inference are the major markers of g, first intertwining with in their respective cycles and differentiating later during the periods of 2–6, 7–11, and 11–20 years, respectively. The implications of these findings for an overarching cognitive developmental/differential theory of human mind are discussed.